Analisis Tingkat Pemahaman dan Miskosepsi Fisika Siswa Pada Materi Suhu dan Kalor Menggunakan Five Tier Diagnostic Test di SMAN 1 Brang Rea - Syahratinnur; Zohdi, Ahmad; Kafrawi, Muhammad (CAHAYA: Journal of Research on Science Education, 2023)
This study aims to analyse the level of understanding and misconceptions of students using the five tier diagnostic test instrument on temperature and heat material. The research method used was descriptive quantitative research. The research was conducted at SMAN 1 Brang Rea with the number of participants as many as 25 students of class XI MIA 1. The instrument used in this research is a five tier diagnostic test of 20 items.  Based on the results of the analysis of this instrument can not only analyse misconceptions but also can analyse students who fully understand, partially understand and do not understand the concept. So that the results of the diagnostic test analysis of students obtained a full understanding level of 38.93%, and a misconception level of 38.93%. Partially understood by 13.33% and did not understand the concept by 8.80%. The cause of misconceptions is mostly caused by one's own thinking because the average confidence level of the causal source for one's own thinking has a greater value than the other causal sources. Although the percentage of misconceptions is moderate, there are still students who experience misconceptions on the material.